Pengaruh Kualitas Pelayanan, Kepercayaan, Harga, Dan Promosi Terhadap Kepuasan Pelanggan Shopee Food (Studi Kasus Mahasiswa Universitas Islam Malang) - Rahman, Muhammad Fahrozi; Arifin, Rois; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract In the era of globalization, the development of communication technology and the internet is encouraging changes thought patterns in human life. The Shope food application can collaborate with offline stores partners who want to collaborate with Shopee food and this can create benefits for both parties. The aim of this research is to understand and analyze services quality, trust, price, and promotion, which simultaneously and partially influence customer satisfaction. The population in this research is Shopee food customer who have and have used the Shopee food application. Approach method using a non-probability sampling technique, namely purposive sampling, which is a sample collection technique based on certain criteria using a questionnaire distributed to 90 respondents and using the SPSS analysis tool. The research results show that the variables services quality, trust, price, and promotion have significant effect on Shopee food customers satisfaction. This is proven by partial and simultaneous hypothesis testing. This research still cannot fully reveal the factors that the influence customer satisfaction with Shopee food. The independent variable in this research can only influence the dependent variable by 69% so there are still 31% variables or other factors that can influence customer satisfaction. Keywords : Services Quality, Trust, Price, Promotion, Customer Satisfaction